NATURAL REALGAR AND AMORPHOUS ASS OXIDATION KINETICS - Lengke M.F.; Tempel R.N. (My University, 2003)
The oxidation rates of natural realgar and amorphous synthetic AsS by dissolved oxygen were evaluated using mixed flow reactors at pH 7.2 to 8.8 and dissolved oxygen contents of 5.9 to 16.5 ppm over a temperature range of 25 to 40°C. The ratios of As/S are stoichiometric for all amorphous AsS oxidation experiments except for two experiments conducted at pH ~8.8. In these experiments, stoichiometric ratios of As/S were only observed in the early stages of AsS (am) oxidation whereas lower As/S ratios were observed during steady state. For realgar oxidation experiments, the As/S ratio is less than the stoichiometric ratio of realgar, ranging between 0.61 and 0.71. This nonstoichiometric release of As and S to solution indicates that realgar oxidation is more selective for S after the rates of oxidation become constant. All measured oxidation rates at 25°C can be described within experimental uncertainties as follows: Table 1 Rate ExpressionActivation Energy (kJ/mol)R(Realgar/As) = 10-9.63(+/-0.41)[DO]0.51(+/-0.08)[H+]-0.28(+/ -0.05)64.2 +/- 9.8R(Realgar/S) = 10-9.74(+/-0.35)[DO]0.54(+/-0.05)[H+]-0.31(+/ -0.04)62.2 +/- 9.0R(AsS(am)) = 10-13.65(+/-0.82)[DO]0.92(+/-0.08)[H+]-1.09( +/-0.10)124 +/- 18.8where R signifies the steady-state oxidation rate (mol m-2s-1), [DO] is dissolved oxygen concentration (M), and [H+] is the proton concentration (M).Arsenic (III) and As(V) are both present in solution, and As(III) is the dominant species in most experiments. Intermediate sulfur species besides sulfate, sulfite, and thiosulfate are the important products during realgar and AsS (am) oxidation.Comparison of realgar and AsS (am) oxidation rates shows that at similar conditions, the rates of AsS (am) are always faster by about a factor ranging from 2 to 38. The oxidation of realgar involves breaking bonds in the realgar crystal, whereas AsS (am) oxidation does not include crystallographic framework destruction due to the amorphous nature of the solid.
Keywords: realgar